PENGARUHKUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN MEMBELI AIR MINUM DALAM KEMASAN MEREK SMS PADA MASYARAKAT VII KOTO SUNGAI SARIK KABUPATEN PADANG PARIAMAN - Yanti Murni (Menara Ilmu, 2017)
This study aims to determine how much influence the quality of products, price and promotion partially to the decision to buy AMDK Brand Sms and the influence of product quality, price and promotion simultaneously to the decision to buy AMDK Brand Sms. This type of research is associative research. This research method is quantitative method. The population in this study is all consumers or customers who buy and consume AMDK Brand SMS Kec. VII Koto Sungai Sarik., Where the sample is 100 respondents. Data collection techniques were conducted with interviews and questionnaires. The data was processed using SPSS version 17. The result showed that the quality of product, price and promotion had a positive effect partially to the decision to buy AMDK Brand Sms and product quality, price and promotion have positive effect simultaneously to the buying decision of AMDK Brand Sms. With multiple linear regression is Y = 0,264 + 0,120 + 0,187 + 0,575 and coefficient of determination give contribution equal to 57,9%. With the positive relationship between product quality, price and promotion have a positive effect on buying decision of AMDK Brand Sms, hence expected to company can improve product quality, affordable price and also aggressive promotion so that it can generate buying interest of consumer or customer.Keywords: Product Quality, Price, Promotion, Buying Decision.